2019
DOI: 10.32604/jrm.2019.00001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Polypropylene Composites Reinforced with Macadamia Nutshell Fibers

Abstract: The use of natural fibers as an additive in polymeric matrices has attracted interest of the automotive industries, for its low cost, mechanical properties, biodegradability and lightness. However, the hydrophilic nature of the fiber makes polymer compatibility difficult. Fiber surface treatments can be used to enhance the fiber/matrix interface. In the present work, polypropylene (PP) composites reinforced with fibers from macadamia nutshell were obtained and characterized. Macadamia nutshell fibers were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…PP has become the most important thermoplastic material in the automobile industry [11]. PP homopolymers, random copolymers and impact copolymers are used in products such as automotive parts and battery cases, carpeting, electrical insulation and fabrics [12]. Moreover, the application of PP in the automobile market is the largest [13].…”
Section: Introductionmentioning
confidence: 99%
“…PP has become the most important thermoplastic material in the automobile industry [11]. PP homopolymers, random copolymers and impact copolymers are used in products such as automotive parts and battery cases, carpeting, electrical insulation and fabrics [12]. Moreover, the application of PP in the automobile market is the largest [13].…”
Section: Introductionmentioning
confidence: 99%
“…It was noted clusters of sclerenchymatous fiber cells with hollow cavities that previously existed as the cell's lignin-rich inclusions, and undamaged sections of polyhedral sclereid cells joined to their neighbors via their faces. 4,30 The fiber presented some pits assigned to water and nutrients transport, 9 common in sclerenchymatous fiber cells. 4,30 The optical microscopy of MNbased LDPE composites showed spherulites increasing with the fiber loading, which is related to better phase dispersion between filler/matrix.…”
Section: Composites Processing and Morphologymentioning
confidence: 99%
“…The agroindustrial crop's valorization is interesting for synthetic chemistry, perfumery, cosmetics, biomedicine, and energy industries. Some studies reported techno‐economic valorization of nutshells residues, such as, macadamia, 3–9 pistachio, 10,11 pecan, 12–17 almond, 18 cashew, 19–21 cedar, 22 oak, 23 fox 24 for catalytic pyrolysis, wastewater treatment, bio‐fillers in a polymeric matrix, microporous sorbents, preparation of carbon‐based products, biochar, supercapacitor for powering electronic devices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations